Environmental analysis of deforestation in an agricultural settlement in the Cerrado (State of Mato Grosso, Brazil) (Terr@ Plural, 2020)
The study aimed to analyze the spatial and temporal variation of the ‘Cerrado’ vegetation cover of the Carimã Agricultural Settlement in Rondonópolis (State of Mato Grosso) employing the NDVI (Normalized Difference Vegetation Index). In 22 years, about 18.2% of the vegetation was removed. In 1995, before the settlement, the vegetation represented 34.4%; in 2017 it remained 18% of the total area. This process has led to major transformations in the region and even in local populations, especially concerning the different land uses and occupations. The suppression of vegetation was linked to uses for agriculture and tourism, with exploration practices that may have contributed to the loss of the Cerrado ecosystem functions.
Keywords: vegetation cover; NDVI; conservation; land uses and occupation